Perencanaan dan Perancangan Pusat Pelatihan dan Pertunjukan Kesenian Khas Kabupaten Tabanan di Kecamatan Kediri, Tabanan - I Gusti Made Candra Sedana Candra; I Nyoman Warnata; I Wayan Runa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
The island of Bali is an island that has a variety of beautiful and diverse tourist destinations. Besides being famous for its tourist destinations, the island of Bali is also famous for its arts and traditions. . For example, in Tabanan Regency, there are 7 types of distinctive arts based on the results of an interview with Wayan Muder as Head of the Arts Division of the Tabanan Regency Culture Service, stating that there are 7 types of distinctive arts, including Okokan Tektekan, Andir Legong Dance, Cerekuak Baris Dance, Rejang Swing Dance, Mandolin Art, Kentungan Art, Leko Kusuma Sari Art. From the potential of the existing typical arts, it can be developed again as a show to support tourism in the Tabanan Regency area in particular. From the potential that can be developed, it is not supported by the existence of adequate training center facilities and performing arts. So the results of the existing problems can be concluded that there is a need for training center facilities and typical arts performances of Tabanan Regency to be a means of supporting and developing culture as well as a means of supporting tourism. as an effort to increase literacy, especially the younger generation to preserve and develop arts and culture in their area, as a gathering place for activists and art communities in Tabanan Regency, as well as a forum to facilitate the Community Arts Festival which is scheduled to be held every year.